ECO EFFICIENCY OF ETAWA CROSSBRED GOAT CARRYING CAPACITY IN VILLAGE GROUP SYSTEM AT YOGYAKARTA IN INDONESIA - Tri Anggraeni Kusumastuti (Caraka Tani: Journal of Sustainable Agriculture, 2009)
This research was conducted to describe condition of goat carrying capacity, with pen efficiency, tree leaves and water availibility so goat carrying capacity sustainability of Etawa Crossbreed goat at Yogyakarta can be known. It located in Nganggring, Kemiri Kebo and Sukorejo subvillage taken with purposive sampling method. Analytical tool used was table analysis. Limited labor in raising caused dominant management by head of household that make the goat cannot meet pen density standard. Tree leaves availibility in village group system is not sufficient for existed goats so farmer should look for tree leaves input from public area. Sandy land and often land slide make naturally uncontinuous water availibility. Although carrying capacity of goat in village group system pen, tree leaves, and water is not efficient, pen and tree leaves have met sustainability of Etawa crossbreed goat in village group system while water availibility have not supported sustainability.